Karakteristik Mineraloid Opal Limbong, Kabupaten Luwu Utara, Provinsi Sulawesi Selatan - Alam Budiman Thamsi; Muhammad Aswadi; Habibie Anwar; Hasbi Bakri; Muhamad Hardin Wakila; Andi Fahdli Heriansyah (Jurnal Geomine, 2020)
Opal is classified as gems that are scattered in several places in the world and specifically in Indonesia is located in Banten, West Java Province and in Limbong, South Sulawesi Province. Opal in Limbong, North Luwu Regency, South Sulawesi Province has never been conducted research, so researchers are interested in conducting research. This research aims to determine the classification of opal mineraloids, host rock, and know the opal mineraloid paragenesis in the Limbong area, Luwu Regency North, South Sulawesi Province. The research method is carried out sampling in the field—laboratory analysis using Petrographic analysis and XRD analysis. The results of the study in the laboratory are then processed to answer the research objectives. The results obtained by opal mineraloid carrier rocks are andesite rocks with a mineral composition consisting of plagioclase, k-feldspar, biotite, muscovite, and quartz. The microscopically visible textures are euhedral, myrmekite, radiated, colloform, and banded. Based on XRD data, the main peak is at 2 Ø: 21.62 with a price of d: 4.0626; the second peak at 2 Ø: 25.16 with a value of d: 3.5147. Another peak with low intensity and bias at 2 Ø: 65.08, with a value of d: 1.4247, is classified as opal-C.